“To not feel fake, it can’t be fake”: co-creation of a harm reduction, peer-delivered, health-system intervention for people who use drugs - J. Deanna Wilson; Stephanie P. Klipp; Kelsey Leon; Jane M. Liebschutz; Jessica Merlin; Cristina Murray-Krezan; Sommer Nolette; Kristina T. Phillips; Michael Stein; Nate Weinstock; Megan Hamm (Harm Reduction Journal)
Abstract Background People who use drugs (PWUD) continue to experience not only high overdose rates but also growing infectious complications. In response, there has been a growing focus on increasing access to harm reduction resources, particularly among hospitalized PWUD. However, there is limited data on how best to integrate harm reduction into hospital settings. We describe using a Design Sprint, a human-centered design process, to co-create an intervention with people who have lived experience (PWLE) focused on improving access and adoption of harm reduction behaviors for hospitalized PWUD. Methods We recruited a sample of PWLE from Pittsburgh, Pennsylvania. We recruited a total of 14 participants over a 3-week period from March to April 2024. There were four Design Sprint sessions, two-hours in length, delivered via HIPAA-compliant zoom. Participants identified intervention components, sketched the intervention, and prototyped the planned intervention process. Sessions were recorded and transcribed verbatim. The team identified intervention components and key themes using thematic analysis. Results There were 14 PWLE (mean age 40.4 years; majority white) who participated in at least one Design Sprint session. Participants conceptualized an intervention delivered by a THRIVE navigator who establishes rapport, identifies what if any goals the participant may have, offers information from a menu of harm reduction topics, and helps participants create a Wellness Plan focused on achieving their goals and overcoming likely barriers. The THRIVE navigator will then follow-up via weekly text messages. There were four additional themes that informed intervention content and implementation. These were related to the hospital being experienced as a hostile environment to PWUD; the value of health information being delivered by PWLE who can speak authentically; the importance of creating a flexible participant-led intervention offering a range of content; and the importance of neutrality to building authenticity and attaining participant buy-in. Conclusions The Design Sprint process allowed for rich input from PWLE on the design, scope, content, and implementation of the THRIVE intervention. Findings highlight the importance of a peer navigator role to embody relational harm reduction and guide THRIVE participants in education and goal setting around a host of wellness-related behaviors.